Ruthenians (the Rus') in the kingdom of Hungary (11th to mid- 14th century) : settlement, property, and socio-political role - Voloshchuk, Myroslav, 1979- (East Central and Eastern Europe in the Middle Ages, 450-1450,, 2021)
This book presents a collective portrait of the inhabitants of Árpádian- and Angevin-era Hungary identified by their countrymen as Rutheni. Many members of this group hailed from the lands of Halych, Chernihiv, Kyiv, and Volhynia, and migrated to Hungary under the pressure of circumstances, eventually carving out for themselves a position of prominence in the kingdom's social hierarchy and political affairs. Drawing on a range of sources, this is the first work to make extensive use of Latin-language documents to throw light on the vicissitudes of the life of Rus' settlers and those bearing Rus'-related names or bynames in medieval Central Europe, revealing their important role in contemporary social and political life.